Self-navigating the “Island of Reil”: a systematic review of real-time fMRI neurofeedback training of insula activity - Yuan Zhang; Benjamin Becker; Keith M. Kendrick; Qiong Zhang; Shuxia Yao (Translational Psychiatry)
Abstract Real-time fMRI (rtfMRI) neurofeedback (NF) is a novel noninvasive technique that permits individuals to voluntarily control brain activity. The crucial role of the insula in emotional and salience processing makes it one of the most commonly targeted regions in previous rtfMRI studies. To provide an overview of progress in the field, the present review identified 25 rtfMRI insula studies and systematically reviewed key characteristics and findings in these studies. We found that rtfMRI-based NF training is efficient for modulating insula activity and its associated behavioral/symptom-related and neural changes. Furthermore, we also observed a maintenance effect of self-regulation ability and sustained symptom improvement, which is of importance for clinical application. However, training success of insula regulation was not consistently paralleled by behavioral/symptom-related changes, suggesting a need for optimizing the NF training protocol enabling more robust training effects. Principles including inclusion of a well-designed control group/condition, statistical analyses and reporting results following common criteria and a priori determination of sample and effect sizes as well as pre-registration are also highly recommended. In summary, we believe our review will inspire and inform both basic research and therapeutic translation of rtfMRI NF training as an intervention in mental disorders particularly those with insula dysfunction.